Determination of access to medicines for children living on poor households of Peninsular Malaysia - Asmalita Syaiful (Universiti Sains Islam Malaysia, 2024)
Thesis (M.Sc)-- Faculty of Medicine and Health Sciences, Universiti Sains Islam Malaysia, 2015